Translation of English Idioms in Novel The Lion the Witch and The Wardrobe and Its Translation - Armita Ayu Sekarsari (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research examines the English idioms found in the novel The Lion the Witch and TheWardrobe and their translation. The aim is to classify the kinds of idiomatic expressionand their Indonesian translation. This research uses descriptive-qualitative method. Dataare the sentences which contain English idioms and their translation. Data sources are thenovel The Lion, the Witch, and The Wardrobe and its Indonesian translation (Sang Singa,Sang Penyihir dan Lemari) limited from chapter one to six. The technique of collectingdata was documentation. The technique of analysis data used comparison method. Theresult shows that the types of idiom found in this novel namely irregular form clearmeaning, regular form unclear meaning, and irregular form unclear meaning and they aretranslated accurately in Indonesian in the same types of idiom. From 35 analyzed datasource of chapter one until chapter six in the novel contain idiom, 54,29% data belong tothe first type, 37,14% data belong to the second type, and 8,57% data belong to the thirdtype of idiom. The research results can be applied in teaching learning of translationsubject